2019
DOI: 10.32861/jssr.512.1700.1713
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Validity and Reliability of Motivational Orientation of Differentiated Instruction in English Language Teaching Student Questionnaire (MoDiELT)

Abstract: Recently, the implementation of differentiated instruction had been proposed by Ministry of Education of Malaysia to be implemented across all schools in the country. Consequently, as announced in the Malaysia Education Blueprint (2013) the Ministry had launched a program called Differentiated Teaching and Learning of English Language. After few years of its implementation, a measurement protocol was needed to assess the effectiveness of differentiated teaching approach in the teaching and learning of English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, English learners in Sapan and Mede’s (2022) study demonstrated higher academic achievement scores following the use of differentiated instruction in their classrooms. Kamarulzaman et al (2017) showed that differentiation strategies (e.g., variation of process, product, and content based on learner interests and profiles, varied grouping, and ongoing assessment) were beneficial for English learners who were identified as gifted. The benefits of differentiated instruction for English learners go beyond higher achievement scores.…”
Section: The Importance Of Differentiationmentioning
confidence: 99%
“…For example, English learners in Sapan and Mede’s (2022) study demonstrated higher academic achievement scores following the use of differentiated instruction in their classrooms. Kamarulzaman et al (2017) showed that differentiation strategies (e.g., variation of process, product, and content based on learner interests and profiles, varied grouping, and ongoing assessment) were beneficial for English learners who were identified as gifted. The benefits of differentiated instruction for English learners go beyond higher achievement scores.…”
Section: The Importance Of Differentiationmentioning
confidence: 99%
“…Specht et al ( 2016 ) indicate the specific need for secondary school level TCs’ training on inclusive teaching strategies, since they show lower self-efficacy in relation to inclusive teaching compared to their elementary school counterparts. Finally, DI applications in STEM education at the secondary school level are limited, since most of the research has been conducted on DI in languages and mathematics for primary and middle school (Kamarulzaman et al, 2018 ; Maeng, 2017 ). Thus, the current research is warranted as it addresses teacher education in Ontario, specifically how to differentiate instruction by engaging TCs in developing DI-focused STEM curricula.…”
Section: Introductionmentioning
confidence: 99%